Nanoindentation to determine volume hardness of steel : Monograph - Moshchenok, Vasyl; Pimonov, Igor; Vorobyova, Svitlana (LAMBERT Academic Publishing, 2025)
The monograph is devoted to a comprehensive analysis of methods for determining the hardness of metals and alloys, with a special emphasis on volume hardness during nanoindentation of steel with a sphero-conical indenter. The paper discusses in detail the Brinell, Vickers, Rockwell, and bulk hardness methods, as well as the features of corrected and uncorrected hardness. New approaches to the calculation of volume hardness in the nano- and micro-range are presented, as well as a measuring device and an author's program for processing the results. The experimental part contains indentation diagrams of steel samples of different hardness levels and the results of bulk hardness calculations. The quantitative parameters of the indentation size effect (ISE) with increasing load during indentation in the nano- and micro-range were determined, and a significant excess of recovered hardness compared to unrecovered hardness was recorded up to 57%. The conclusions presented in the monograph are of practical importance for the evaluation of the mechanical properties of materials, especially in the field of nanotechnology and engineering.
Keywords: mechanical engineering; production technology